The Fragility of Turkish Political Structures – The AKP Closure Case - Turkmen, Seref (European Scientific Journal, ESJ, 2023)
For the Justice and Development Party (AKP), one of the most serious challenges in its history was the dissolution lawsuit against the party in 2008. This was not because there would have been no precedent in Turkey for banning the various political parties, but because by then one could speak of a government party with serious social support that had already won two parliamentary elections. Since the founding of the Republic of Turkey, it has not been uncommon for one or another political formation to be banned, but at times they have reactivated themselves under a different name. In fact, the initial, one-party era of the republic was also created by the situation provoked by the founder of the state, Mustafa Kemal Ataturk, who banned rival, opposition parties that threatened his position. Even since the introduction of the multi-party system in 1946 and the first multi-party election in 1950, nearly three dozen parties have been doomed. These included Kurdish separatist groups, parties with communist ideologies, but also the AKP’s moderate Islamist predecessors. It has also happened that the leaders of a military coup have decided to ban some parties, but it has also been the case that in a peaceful and democratic period the prosecution has initiated the same in the Constitutional Court claiming that one party or another is opposed to the most basic republican principles. Yet the case of the AKP was special because, in the case of a party that had been ruling alone for six years, it was still surprising that it was not its political opponent trying to overthrow its power, but the legal nomenclature attached to the old elite. In the second half of the 2000s, the AKP was still taking reluctant steps towards democratic opening, and it was far from the authoritarian style and centralization efforts that characterize it today, yet it can be said that they had fairly stable political positions. Of course, it is no coincidence that several things have weakened the situation of the AKP, and the party leaders could not have felt that they were surviving this crisis in a political sense. There was a chance that the organization would actually cease to function and the Prime Minister and the President of the Republic would be banned from practicing public affairs for up to 5 years. The legal process aimed at banning the party has resonated heavily in Turkey, but has come as a real surprise only to the Western public opinion. The purpose of this article is to look at why the Turks were so laconic about the situation and why it has caused so much uproar in Europe and America. At the same time, it will be possible to see the main differences between Western and Turkish democratic traditions.As the wrangling around the ban of the AKP excited foreign observers more than domestic experts, the literature used for the article was also mostly in English, and only a small number of works in Turkish were taken into consideration.